2015
DOI: 10.1111/jch.12678
|View full text |Cite
|
Sign up to set email alerts
|

DoesQRSVoltage Correction by Body Mass Index Improve the Accuracy of Electrocardiography in Detecting Left Ventricular Hypertrophy and Predicting Cardiovascular Events in a General Population?

Abstract: The authors assessed the value of body mass index (BMI) correction of two electrocardiographic criteria in improving detection of left ventricular hypertrophy (LVH) and prediction of cardiovascular and all-cause mortality in the Italian study Pressioni Arteriose Monitorate E Loro Associazioni (PAMELA) population. At entry, 1549 patients underwent diagnostic tests, 24-hour ambulatory blood pressure (BP) monitoring, standard electrocardiography, and echocardiography. The BMI-corrected Cornell voltage and Sokolow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
11
2
Order By: Relevance
“…Moreover, whether this approach is appropriate in subjects of African ancestry, where the dampening effects of obesity on QRS voltages are particularly striking, 20 is unknown. In keeping with that noted in European populations, we show an improved performance (AUC for ROC) for LVH detection 21,22 using the QRS voltage-BMI product. We nevertheless demonstrate that the best overall performance for LVH detection is by modifying the QRS voltages for R aVL and Lewis criteria in those with BMI ≥29 kg/m 2 by the aforementioned mathematical formula.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, whether this approach is appropriate in subjects of African ancestry, where the dampening effects of obesity on QRS voltages are particularly striking, 20 is unknown. In keeping with that noted in European populations, we show an improved performance (AUC for ROC) for LVH detection 21,22 using the QRS voltage-BMI product. We nevertheless demonstrate that the best overall performance for LVH detection is by modifying the QRS voltages for R aVL and Lewis criteria in those with BMI ≥29 kg/m 2 by the aforementioned mathematical formula.…”
Section: Discussionsupporting
confidence: 87%
“…21,22 In the present study, BMI showed no relations with Sokolow-Lyon voltages in those with BMI <29 kg/m 2 and inverse relations with Sokolow-Lyon voltages in those with BMI ≥29 kg/m 2 . Moreover, BMI showed weak relations with Cornell voltages, with no differences in the strength (r value) or slopes (β-coefficients) of these relations in those with BMI <29 kg/m 2 as compared with those with BMI ≥29 kg/m 2 .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In contrast to the above finding, Cornell voltage in middle-aged subjects was the only ECG index that was associated with LVH detection irrespective of indexation [46]. Another plausible explanation could be the fact that the evidence indicates that the sensitivity of several ECG criteria decreases from normal-weight to overweight and obesity [47]. In this regard, a recent study from Italy found that BMI-corrected Sokolow-Lyon voltage and Cornell voltage criteria provided better results for detection of echocardiographic LVH compared with unadjusted parameters [47].…”
Section: Discussioncontrasting
confidence: 48%